2013
DOI: 10.1515/htmp-2012-0146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Heat Treatment Conditions on Fatigue Behavior of AA7075 Alloy

Abstract: In this study, the effect of different heat treatment processes applied to AA7075 alloys on the fatigue behavior was examined. The processes applied to AA7075 aluminum included annealing (O), high temperature pre-precipitating (HTPP), artificial aging (T6), retrogression and re-aging (RRA). The annealing heat treatment was performed for 2 hours at 500°C and samples were cooled in the furnace. In the artificial aging (T6) process, after the samples were solution treated for 2 hours at 500°C, they were quenched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
(26 reference statements)
1
10
0
3
Order By: Relevance
“…• C for 24 h [11]. The aged samples are subjected to standard metallographic processes for characterization studies and were etched with 2 ml HF, 90 ml distilled water, 5 ml HNO 3 and 3 ml HCl solution for 50-60 s. Etched samples are examined through SEM+EDS, XRD, and hardness measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• C for 24 h [11]. The aged samples are subjected to standard metallographic processes for characterization studies and were etched with 2 ml HF, 90 ml distilled water, 5 ml HNO 3 and 3 ml HCl solution for 50-60 s. Etched samples are examined through SEM+EDS, XRD, and hardness measurements.…”
Section: Methodsmentioning
confidence: 99%
“…• C for 24 h ageing process [7]. At the end of the process, since corrosion sensitivity of the alloy increases, T73 heat treatment is developed to increase corrosion resistances of these types of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, it was reported that different phases such as Al 7 Cu 2 Fe and Al 2 CuMg formed in the structure in addition to MgZn 2 precipitates [8,10]. In another study, it was noted that it is not possible to say that these precipitate phases have formed during the ageing treatment [11]. Figure 2b shows that the hardness values of the alloys, aged at different ageing temperatures for 24 h, increase by the increasing ageing temperature.…”
Section: Resultsmentioning
confidence: 88%
“…A quenching rate above the critical quenching rate of the work piece material was seen to be essential in order to avoid the generation of coarse precipitates on the grain boundaries, which diminishes the artificial ageing response of the work piece material. Furthermore, many researchers have selected water as the quenching medium and artificial ageing process as the further process of gaining the mechanical strength and hardness because water is cheap, readily available and nontoxic [30].…”
Section: Quenchingmentioning
confidence: 99%